Efectividad de un proyecto de colaboración entre atención primaria y salud mental para mejorar el registro de factores de riesgo cardiovascular en pacientes con psicosis()() - Viñas Cabrera, Lidia (Aten Primaria, 2013)
OBJECTIVE: To evaluate the effectiveness of a joint team intervention between primary care (PC) and mental health (MH) to improve information on cardiovascular risk factors (CVRF) in psychotic patients. DESIGN: Multicenter before-after intervention study. LOCATION: Seven primary care and 2 mental health centers in Barcelona participated. PARTICIPANTS: All patients between 18-65 years old with a confirmed diagnosis of psychosis assigned to PC teams (n = 690) are included. INTERVENTION: Shared clinical sessions, developing a joint GP-MH protocol and implement it. PRIMARY MEASUREMENTS: Variables: Gender, age, number of Appointments per center/year, smoking, blood pressure, body mass index (BMI), total cholesterol, HDL cholesterol, triglycerides, glucose, waist circumference (WC), Cardiovascular Risk. ANALYSIS: Comparison of CVRF records from 2008 to 2010 using statistical tests for paired data. Calculation of CVRF prevalence in accordance with metabolic syndrome criteria and the criteria for referral to GP. RESULTS: The mean age was 42.3 (SD 11.4) years, with 67% males. All CVRF significantly Increased in clinical notes, particularly all blood test parameters and WC. More than 35% of patients had a CVRF according to metabolic syndrome criteria. Criteria to refer to PC physician (2010) identified: obesity 51.9%, 23.9% hypertension, high cholesterol 20.4% and 11.6% diabetes. CONCLUSIONS: CVRF recording improvement. High percentage of patients needed GP intervention due to a CVRF.